1998
DOI: 10.1377/hlthaff.17.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Access To Care: How Much Difference Does Medicaid Make?

Abstract: Using the 1994 Robert Wood Johnson Foundation National Access to Care Survey, we examine the likelihood of having a usual source of care, inability to obtain needed care, and number of physician visits for persons with private insurance, Medicaid coverage, and no insurance. Inability to obtain services is surprisingly consistent: For each service, Medicaid enrollees were about half as likely as uninsured persons and about twice as likely as privately insured persons were to report difficulty. For other access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 13 publications
5
50
0
1
Order By: Relevance
“…This indicates an ongoing relationship with a health care provider that offers the potential for care coordination and continuity instead of episodic and fragmented care on an emergency basis. Relatively high levels of Medicaid beneficiaries report a usual source of care (>85%), and these rates are considerably higher than those of the uninsured and somewhat lower than the levels for those with private insurance (7,88,101). Low-income women with Medicaid were more likely to have a usual source of care (85%) than those with private coverage (80%) or no insurance (69%) (53).…”
Section: Medicaid's Impactmentioning
confidence: 96%
See 1 more Smart Citation
“…This indicates an ongoing relationship with a health care provider that offers the potential for care coordination and continuity instead of episodic and fragmented care on an emergency basis. Relatively high levels of Medicaid beneficiaries report a usual source of care (>85%), and these rates are considerably higher than those of the uninsured and somewhat lower than the levels for those with private insurance (7,88,101). Low-income women with Medicaid were more likely to have a usual source of care (85%) than those with private coverage (80%) or no insurance (69%) (53).…”
Section: Medicaid's Impactmentioning
confidence: 96%
“…Analysis of utilization levels within the low-income population reveals striking differentials between the uninsured and Medicaid populations and shows that Medicaid coverage plays a significant role in reducing access barriers generally (7,27,59,101,102) and for women and children as well.…”
Section: Medicaid's Impactmentioning
confidence: 99%
“…21 Although studies have demonstrated Medicaid's effectiveness in reducing the health services use gap between the publicly and privately insured (e.g., having a usual source of care and the number of physician visits), disparities in access to care persist, particularly with respect to the inability to receive care. [22][23][24] Medicaid's low payment rates to providers may limit beneficiaries' choice of providers. 25 In addition, the presence of fewer specialists in rural or isolated regions may compound difficulties in reaching an already limited number of primary care physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing access to care for uninsured individuals and Medicaid beneficiaries provides insight into Medicaid's impact. Medicaid has helped narrow the gaps in access to care for low-income groups, and various access measures show that Medicaid beneficiaries access care at similar rates as those who are privately insured (4,56). Across studies, these findings are particularly strong for children (59,64,66,67,75,85,91,95).…”
Section: Impact On Access To Carementioning
confidence: 99%